Giardia intestinalis Incorporates Heme into Cytosolic Cytochrome b(5) - Pyrih, Jan (American Society for Microbiology, 2014)
The anaerobic intestinal pathogen Giardia intestinalis does not possess enzymes for heme synthesis, and it also lacks the typical set of hemoproteins that are involved in mitochondrial respiration and cellular oxygen stress management. Nevertheless, G. intestinalis may require heme for the function of particular hemoproteins, such as cytochrome b(5) (cytb(5)). We have analyzed the sequences of eukaryotic cytb(5) proteins and identified three distinct cytb(5) groups: group I, which consists of C-tail membrane-anchored cytb(5) proteins; group II, which includes soluble cytb(5) proteins; and group III, which comprises the fungal cytb(5) proteins. The majority of eukaryotes possess both group I and II cytb(5) proteins, whereas three Giardia paralogs belong to group II. We have identified a fourth Giardia cytb(5) paralog (gCYTb5-IV) that is rather divergent and possesses an unusual 134-residue N-terminal extension. Recombinant Giardia cytb(5) proteins, including gCYTb5-IV, were expressed in Escherichia coli and exhibited characteristic UV-visible spectra that corresponded to heme-loaded cytb(5) proteins. The expression of the recombinant gCYTb5-IV in G. intestinalis resulted in the increased import of extracellular heme and its incorporation into the protein, whereas this effect was not observed when gCYTb5-IV containing a mutated heme-binding site was expressed. The electrons for Giardia cytb(5) proteins may be provided by the NADPH-dependent Tah18-like oxidoreductase GiOR-1. Therefore, GiOR-1 and cytb(5) may constitute a novel redox system in G. intestinalis. To our knowledge, G. intestinalis is the first anaerobic eukaryote in which the presence of heme has been directly demonstrated.